HYPNOSIS: AN UNFINISHED CONTROVERSY - Tortosa, Francisco; González Ordi, Héctor; Miguel-Tobal, Juan José (Anales de Psicología / Annals of Psychology, 1999)
Research on the basic underlying characteristics of the hypnotic process has been historically characterized by its controversial nature due to, among other topics, most of the hypnosis researchers have assigned to different conceptions or paradigms on the nature of the hypnosis: (1) the traditional paradigm, which supposes that hypnosis implies an altered state of consciousness; (2) alternative, cognitive- behavioral or sociocognitive paradigm, which argues that it is not necessary to resort to the concept of a special state for the explanation of the hypnotic behavior. Both conceptions have generated different research strategies and experimental outcomes. In the present paper, the historical background which leads to such theoretical controversy are delineated in detail, focused especially on its evolution since animal magnetism to present time